Review of the structural and functional brain changes associated with chronic kidney disease - Michna, M; Kovarova, L; Valerianova, A; Malikova, H; Weichet, J; Malik, J (Physiological research, 2020)
Chronic kidney disease (CKD) leads to profound metabolic and hemodynamic changes, which damage other organs, such as heart and brain. The brain abnormalities and cognitive deficit progress with the severity of the CKD and are mostly expressed among hemodialysis patients. They have great socio-economic impact. In this review, we present the current knowledge of involved mechanisms.
Keywords: rizikové faktory; mozek; chronická renální insuficience; kognitivní poruchy; Animals; lidé; Risk Factors; Humans; zvířata; Cognition Disorders; Renal Insufficiency, Chronic; Brain